The psychology of law: human behavior, legal institutions, and law - Sales, Bruce Dennis (The law and public policy : psychology and the social sciences, 2015)
Introduction -- The law psychological science should study -- Asking the appropriate questions about law -- Incorporating the traditional scientific goals -- Studying the range of explanatory factors -- Using valid and reliable scientific methods -- Comprehensively using psychology to study law : the example of plea bargaining -- Overarching concerns and solutions